(untitled) (Forum Agribisnis, 2025)
Muara Enim Regency is one of the largest rubber producing districts in South Province, but is currently experiencing a significant decline in the amount of rubber land due to land conversion issues. This land conversion is mainly caused by rubber farming income that does not provide adequate economic benefits to meet the needs of farmers. The research objectives were to 1) Analyze rubber farm income 2) Analyze the factors that influence rubber farming income. This study used 112 rubber farmer respondents, with a population of 543 rubber farmers Lubai District. The location was chosen purposely based on the same considerations, namely the sub-district and village that produced the largest decline in the number of rubber land areas and produced the largest rubber production. Data collected in cross section. Analysis of rubber farm income using R/C ratio analysis. Analysis of factors affecting rubber farming income using Weighted Least Square. The results showed that income in the productive plant age group (10.1-15 years) was the greatest compared to other plant age groups. The overall R/C ratio on cash costs and on total costs in all plant groups showed good results with an R/C ratio > 1. Factors that positively affect rubber farm income in Lubai Subdistrict are average production, rubber prices, and land area while factors that negatively affect farm income are labor.